The Chemotherapeutic Potentials of Compounds Isolated from the Plant, Marine, Fungus, and Microorganism: Their Mechanism of Action and Prospects - Ashok K. Shakya; Rajashri R. Naik (Journal of Tropical Medicine)
Research on natural products mainly focuses on developing a suitable drug to treat human disease. There has been a sharp increase in the development of drugs from natural products. Most of the drugs that are available are from the terrestrial origin. Marine natural products are less explored. Oceans are considered as a vast ecosystem with a wide variety of living organisms and natural products that are unexplored. Large numbers of antitumor drugs are from natural sources such as plants, marine, and microorganisms. 80% new chemical entities that were launched over the past 60 decades were from a natural source. In this article, the anticancer potential from the natural source such as plants, fungi, microorganisms, marine, and endophytes has been reviewed. Emphasis is given on the compound from the marine, plant, and of bacterial origin. Finally, we consider the future and how we might achieve better sustainability to alleviate human cancer suffering while having fewer side effects, more efficacies, and causing less harm than the present treatments.